Implementasi React Vite Dalam Pengembangan Antarmuka Sistem Pemesanan Tiket Pesawat Dengan Metode Scrum - Alfa Rizzi, Tegar; Aziz Abdillah, Rafly; Efani Yancandra, Yogi; Wijaya, Melinda; Voutama, Apriade (Jurnal PROCESSOR, 2025)
This research discusses the development of an airline ticket booking information system interface. The Scrum methodology was employed in the interface development process. Scrum was chosen for its ability to divide the development process into several sprints. At the end of each sprint, suggestions and evaluations for subsequent development are produced, thereby continuously enhancing the effectiveness of each development process. The system, developed using React Vite as the main technology, accelerates the development process and improves user experience through React's Single Page Application architecture, which enables smoother and more efficient navigation throughout the website. Another objective of this research was to reduce paper usage by providing a feature to download tickets in digital format using React PDF technology. Beyond this digital ticket feature, the system incorporates several core functionalities, including ticket booking, payment processing, order history tracking, and notification services. The result of this research is documentation of the interface development process based on the Scrum methodology, demonstrating that all developed features are functioning optimally.